(untitled) (Research, Society and Development, 2020)
The intensification of beef cattle production occurs when the productive efficiency of the cow is increased by adjusting the calving season and cows with higher milk production. The objective was to evaluate the effect of the calving date within the birth season and milk production on the productive efficiency of beef cows. Eighty Charolais x Nellore cows and their crosses of 3 to 7 years old, were grouped according to its birth date within the calving season (Early or Late) and milk production (Low = 312 L; High = 448 L up to 63 days lactation). Cows and their calves were weighed at birth, at 63 (early weaning), at 210 and 365 days of age. The cows were kept in natural pasture with a capacity of 0.6 cows with calf at the foot / ha in three paddocks, and the animals were rotated between them every 14 days. The estimated milk production was assessed by manual milking at 21, 42, and 63 days postpartum. The experimental design used was completely randomized in a 2x2 factorial scheme, two calving seasons and two levels of milk production. Calving season and milk production did not influence the weights and average daily weight variations of cows and calves in the different phases evaluated. Early cows at the calving season were superior in reproductive performance than late cows, without milk production influencing this trait. Calves of low production cows needed less milk to produce one kilogram of body weight. The adjusted calve kilograms production for the pregnancy rate of cows is higher for early than later calved cows. Calved cows early in the calving season are more productive in the production of kilograms of body weight.